School Management Collaboration in Managing Student Potential in Nature Schools - Rahmi Dewi; Mada Sutapa (Journal of Education and Teaching Learning, 2026)
This study aimed to analyze the patterns of school management collaboration in managing student potential at Sekolah Alam Kampung Sawah and Pesantren Alam Arrahmah Bondowoso. The inquiry focused on role distribution among school management actors, coordination mechanisms, student potential facilitation strategies, and supporting and inhibiting factors of collaboration. A qualitative approach with a multi-site case study design was employed. Data were collected through in-depth interviews, limited participatory observation, and school documentation. Participants included principals, classroom teachers, supporting teachers, dormitory mentors, administrative staff, and parents. Data were analyzed through data condensation, data display, and thematic conclusion drawing. Trustworthiness was strengthened through source triangulation, technique triangulation, member checking, and document audits. The findings revealed that school management collaboration in managing student potential was enacted through coordination meetings, daily communication, individual assistance, outdoor learning adaptation, and student progress evaluation. Effective collaboration emerged when schools developed participatory leadership, a caring culture, cross-role communication, and consistent student development documentation. The main constraints were limited potential assessment instruments, teacher workload, and uneven understanding of holistic student potential management